Training and assistance of black garlic production in Waru Village, Parung District, Bogor Regency - Sukrianto, Sukrianto; Putri, Dessy Iriani; Permatasari, Tria Astika Endah; Ziva, Danindra; Wahyuni, Sri (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
The Family Empowerment and Welfare Program (PKK) plays an important role in improving family welfare in Waru Village, Parung District, Bogor Regency. Since the COVID-19 pandemic, public awareness of health has increased, making it essential to implement a program for developing innovations in processing garlic into black garlic within the PKK of Waru Village. Black garlic is known to have greater health benefits compared to regular garlic, particularly as an antioxidant and immunity booster. This program involves several stages, including socialization, training on black garlic production, the application of fermentation technology, and assistance to ensure the success of black garlic production and marketing. Evaluation results indicate a significant improvement in participants' knowledge and skills regarding the production process and the benefits of black garlic, as measured through pre-test and post-test assessments. This program is expected to empower the community in the long term, both in terms of health and economic benefits, through the commercialization of black garlic products